A Truncated Molecular Star. Issue 51 (17th July 2017) - Prusty, Soumyakanta; Yazaki, Kohei; Yoshizawa, Michito; Chand, Dillip Kumar
Abstract: A pentanuclear coordination complex assembled from any palladium(II) component and non‐chelating ligands is hitherto unreported. The pentanuclear complex [Pd5 (L1 )5 (L2 )5 ](BF4 )10, 1 reported here was prepared by the spontaneous complexation of [Pd(DMSO)4 ](BF4 )2 with the non‐chelating bidentate ligands 1, 4‐phenylenebis(methylene) diisonicotinate, L1 and 4, 4′‐bipyridine, L2 in a one‐pot method at room temperature. The planar polycyclic complex1 with outer diameters of ≈3 nm is termed as a "molecular star" owing to its resemblance with a pentagram shape. Interim paths leading to the star were also probed to decipher related dynamics of the system. Abstract : High five ! A star‐shaped heteroleptic pentanuclear complex [Pd5 (L1 )5 (L2 )5 ] (BF4 )10 was synthesized in a one‐pot method, by combining [Pd(DMSO)4 ](BF4 )2 with the non‐chelating bidentate ligands 1, 4‐phenylenebis(methylene) diisonicotinate, L1 and 4, 4′‐bipyridine, L2 in an equal ratio. The complex is characterized by NMR spectroscopy, MS and single‐crystal X‐ray diffraction techniques. Interim paths leading to the star were probed to decipher related dynamics of the system.